KEANEKARAGAMAN JENIS VEGETASI PADA KAWASAN HUTAN LINDUNG GUNUNG AMBAWANG KABUPATEN KUBU RAYA PROVINSI KALIMANTAN BARAT - Sularno, .; Fahrizal, .; Iskandar AM, . (JURNAL HUTAN LESTARI, 2016)
The diversity of vegetation which is quite high in some areas of the forest one of which is a protected forest areas Ambawang mountain. Limited data on the diversity of vegetation and standing stock in the mountain protected areas Ambawang make motivastion in this study. Creating a great power to preserve the forest. The purpose of this study was to determine the diversity of vegetation in protected forests Ambawang mountain forests. By using the method used is a double plot squares method, by taking a sample plot vegetation with many examples, which is made of  20 pieces measuring 40 x 40 are placed evenly distributed in accordance with the conditions of the closing of vegetation. Observations find the type of vegetation results showed that in the area of Protected Forest Mount Ambawang found 19 species of trees making forest stands for all levels of forest stands found in 20 plots of observation with the observation area of 3.2 hectares. Keywords:       Type vegetation,  forest protected areas